2013
DOI: 10.1103/physrevd.88.016011
|View full text |Cite
|
Sign up to set email alerts
|

Boundary localized terms in universal extra-dimensional models through a dark matter perspective

Abstract: In universal extra dimension (UED) models with one compactified extra dimension, a Z 2 symmetry, termed KK parity, ensures the stability of the lightest Kaluza-Klein particle (LKP) which could be a viable dark matter candidate. This symmetry leads to two fixed points. In nonminimal versions of UED boundary-localized (kinetic or mass) terms (BLT) for different fields are included at these fixed points and KK parity may be violated. However, BLTs with same strength at both points induce a new Z 2 symmetry which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 75 publications
(148 reference statements)
0
45
0
Order By: Relevance
“…Depending on the parameter values, the LKP can be the level-1 photon (B 1 ), the level-1 Z-boson ( W has too small DM abundance thus is not favored [63]. The expected signal rate of KK DM with, e.g., Xenon nuclei is still well below the existing limits set by XENON100 for spin-independent scattering [63]. Higgs DM in UED models is discussed in Ref.…”
Section: Direct Detectionmentioning
confidence: 99%
“…Depending on the parameter values, the LKP can be the level-1 photon (B 1 ), the level-1 Z-boson ( W has too small DM abundance thus is not favored [63]. The expected signal rate of KK DM with, e.g., Xenon nuclei is still well below the existing limits set by XENON100 for spin-independent scattering [63]. Higgs DM in UED models is discussed in Ref.…”
Section: Direct Detectionmentioning
confidence: 99%
“…For completeness first we describe the general set-up of nmUED with BLTs and as we proceed we point out how to revert to mUED. For a more detailed discussion of the model see [16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Model Descriptionmentioning
confidence: 99%
“…Therefore nmUED has a rich phenomenology compared to the mUED scenario thanks to the presence of the BLT parameters. Some of the recent studies on the phenomenology of the BLTs can be found in [17][18][19][20][21][22][23][24][25][26][27][28]. Now, an important aspect of SM is the absence of flavour changing neutral current (FCNC) interactions at the tree-level.…”
Section: Introductionmentioning
confidence: 99%
“…Various phenomenological studies in the framework of nmUED have been made to constrain non-minimality parameters from the perspective of electroweak observables [13], S, T and U parameters [11,15], relic density [16,17], measurement of decay width of Z-boson to a pair of b-quarks [18], SM Higgs boson production and decay [19] and from the LHC experiments [20,21].…”
Section: Introductionmentioning
confidence: 99%